Narratives of learning experiences experienced in professional and technological education by PROEJA students (Research, Society and Development, 2021)
The work aimed to articulate the life histories of PROEJA students with their experiences in the PtSD, in which we sought to demonstrate the impacts of this course on the lives of these subjects and culminated in an educational product in the form of a short film. To theoretically support this research, we used studies on the pedagogical practices of the EJA in Brazil, conceptual bases of professional and technological education and its contextualization with the EJA, conception of Integrated High School, besides dealing with the experience of methodological work with memory. We used life history as an operational procedure (Severino 2002), and for the study of data captured through the short film, in which it made it possible to identify categories of analyses, namely: work, family, difficulties and prejudices, realization of dreams), we used discourse analysis (Bartelmebs 2013). From the analyses performed it was possible to visualize that the short film served as a source of inspiration and motivation for the students of THE PROEJA of IFRN, Mossoró campus. Thus, we observed that the short film presented fulfills the function of promoting a link between the life histories of the subjects projected in the video and the students of PROEJA, motivating them to follow the completion of their course.